The Empirics of Foreign Exchange Intervention in Emerging Markets The Cases of Mexico and Turkey - Karacadag, Cem (International Monetary Fund, 2004)
This paper analyzes the effects of intervention on the level and volatility of the exchange rate in Mexico and Turkey, two emerging countries that have floating exchange rate regimes. The paper finds mixed evidence on the effectiveness of intervention. In Mexico, foreign exchange sales have a small impact on the exchange rate level and raise short-term volatility, while in Turkey, intervention does not appear to affect the exchange rate level but reduces its shortterm volatility. In both cases, the findings are consistent with officially stated policy objectives, which aim to minimize the effect of intervention on the exchange rate, but cast doubt on claims that intervention is a useful tool for smoothing volatility. Although these findings cannot be generalized to other emerging markets, intervention''s apparently limited effectiveness highlights the need for central banks to use their scarce foreign reserves selectively and parsimoniously